Programming Teaching Using Flowcharts in a Simulated Environment Focused on Introducing Practical OBR - Fabro, João; Paula, Eli; Dias, Álefe; Skora, Lucas (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Educational robotics is an approach that uses robotics as a mean to aid in the learning process, fundamentally of more abstract concepts. In the practical OBR - the Brazilian Robotics Olympiad - students from ages 6 to 18 participate by constructing/programming robots, using concepts of physics, mathematics, and programming, in order to understand complex and abstract concepts. In this paper, an approach to aid in introductory programming courses, focused on students that had never had any contact with computer programming, is presented. The approach presents programming concepts using icons and "flowcharts", and a 3D robotics simulator (V-REP), that has free educational use. The Robotic Operating System (ROS) is also used. The programs to control the robot are developed by graphically constructing fluxograms on the visual editor, and then following the execution of programs using the simulated robot, step by step. Experiments were performed with students in order to evaluate the proposed approach, and the students found the proposal intuitive and easy to understand.